Effects of an orientation illusion on motor performance and motor imagery. - Glover, S; Dixon, P; Castiello, U; Rushworth, M (2005)
Although the effect of visual illusions on overt actions has been an area of keen interest in motor performance, no study has yet examined whether illusions have similar or different effects on overt and imagined movements. Two experiments were conducted that compared the effects of an orientation illusion on an overt posture selection task and an imagined posture selection task. In Experiment 1 subjects were given a choice of grasping a bar with the thumb on the left side or right side of the bar. In Experiment 2 subjects were instructed to only imagine grasping the bar while remaining motionless. Subjects then reported which side of the bar their thumb had been placed in imagined grasping. Both the overt selection and imagined selection tasks were found to be sensitive to the orientation illusion, suggesting that similar visual information is used for overt and imagined movements, with both being sensitive to an orientation illusion. The results are discussed in terms of the visual processing and representation of real and imagined actions.